PLANNING OF EXTENT AND FINANCIAL EXPENSES FOR DELIVERY OF HEALTH CARE IN HOSPITALS AT THE FEDERAL AND REGIONAL LEVELS - M. V. Sura (IRBIS LLC, 2016)
Introduction. Extent and financial expenses for the delivery of health care in hospitals are planned within the framework of the annual approval of the Program of state guarantees of the free public delivery of health care (PSG), as well as of Territorial programs of state guarantees of the free public delivery of health care (TPSG). The research purpose is to carry out the comparative analysis of norms of extent and financial expenses for the unit of delivery of health care in hospitals, established at the federal and regional levels within the frameworks of PSG and TPSG in 2015. Materials and methods. Comparative analysis of norms of the delivery of health care in hospitals (norms of extent and financial expenses per extent unit), established by PSG and TPSG for 2015. The above regional norms have been analyzed in eight entities of the Russian Federation (Моscow, Saint-Petersburg, Stavropol region, Novosibirsk region, Khabarovsk region, Sverdlovsk region, Volgograd region, Nizhny Novgorod region), representing eight federal districts of the Russian Federation. Results. PSG and TPSG annually undergo changes, including those related to norms of the delivery of health care and extent of financial expenses, including the segment of hospital health care. During the last years, not only values of such indices have changed (reduction of norms of extent, as well as the growth of norms of financial expenditures per extent unit in hospital conditions), but also its measurement units (transition from bed days to hospitalization cases). The extent norm, established by PSG in 2015, was 0,193 case per one resident and 0,172 case per one insurant per year; the norm of financial expenses was 63 743,8 rubles and 22 233,1 rubles per one case of hospitalization at the expense of budgetary funds and of funds of the compulsory health insurance system accordingly. Entities of the Russian Federation establish, within TPSG frame works, norms of extent and financial expenses for the delivery of health care in hospitals. Actually, the values of such indices can differ from norms, established at the federal level. In this connection, the budgetary part of norm, not like the compulsory health insurance segment, can considerably differ from federal norms as to extent of health care and financial expenditures. Тhe territorial financial norm of the hospitalization case at the expense of compulsory health insurance funds was not lower than the federal norm in any of the analyzed entities of the Russian Federation.